Empowering Nursing Practices: Enhancing Patient Care Through Knowledge, Attitude and Practice Towards Urinary Catheterisation in Taicang City - Lihong Zhang; Hong Zhang; Yaxuan Wang; Hui Li; Ting Liu; Jingjing Qian; Chi Wang (Nursing Open)
ABSTRACT Aim To assess the knowledge, attitude and practice (KAP) towards unnecessary urinary catheterisation among nurses in Taicang City, China. Design Cross‐sectional study. Methods This study included nurses from our hospital and was conducted between February 2023 and June 2023. Data Sources A self‐administered questionnaire was designed to collect their demographic characteristics and KAP. Results A total of 233 valid questionnaires were collected. The mean KAP scores were 13.44 ± 1.62 (possible range: 0–17), 45.28 ± 3.87 (possible range: 10–50) and 43.85 ± 5.98 (possible range: 10–50), which indicated moderate knowledge, positive attitude and proactive practice, respectively. The Pearson's correlation analysis showed positive correlations between knowledge and attitude (r = 0.253, p < 0.001), knowledge and practice (r = 0.279, p < 0.001), as well as attitude and practice (r = 0.441, p < 0.001). Partial correlation analysis adjusted for age, gender, department, working experience and experience in treating patients with catheter‐associated urinary tract infections also showed positive correlations among KAP. A structural equation modelling showed that both knowledge (β = 0.501, p = 0.047) and attitude (β = 0.691, p < 0.001) had direct effect on practice. Conclusion This study found moderate knowledge, positive attitude and proactive practice among the participants. Both knowledge and attitude might affect their practice. Impact We wanted to know the knowledge, attitude and behaviour of nurses in Taicang City towards unnecessary catheterisation. Moderate knowledge, positive attitude and proactive practice were found among the participants. The findings would provide evidence for policymakers to develop targeted educational intervention to improve nurses’ practice and might improve the outcomes of patients. Reporting Method This study was reported to be adhered to the STROBE guideline. Patient or Public Contribution No patient or public contribution. Implications for the Profession and/or Patient Care Targeted educational intervention was needed to improve nurses’ practice.